HERMETO: A NL Analysis Environment - Martins, Ronaldo Teixeira; Hasegawa, Ricardo; Nunes, Maria das Graças Volpe (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2004)
This paper describes HERMETO, a computational environment for fully-automatic, both syntactic and semantic, natural language analysis and understanding. HERMETO converts lists into networks and has been used to enconvert Brazilian Portuguese and English sentences into Universal Networking Language (UNL) hypergraphs.